Determinan Penyerapan Tenaga Kerja Sektor Industri Manufaktur Di Kabupaten/Kota Jawa Tengah Tahun 2018-2021 - Galuh Pamungkas Samiyarso (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2022)
Using panel data regression and the Fixed Effects Model (FEM) method, the purpose of this study is to ascertain how education, the Human Development Index, the number of businesses, and the GRDP of the manufacturing industry sector have an impact on the workforce of the manufacturing industry sector in the Regency/City of Central Java from 2018 to 2021.This study found that the workforce in the manufacturing industry sector in Central Java is not affected by the district minimum wage, the Human Development Index, or education, while the GDP of the manufacturing industry sector and the number of companies have an impact.